Heart involvement in transfusion-dependent beta-thalassemia with conventional echocardiography - Hossein Esfahani; Asadolah Tanasan; Mina Rezanejad; Saadat Torabian (Babol University of Medical Sciences, 2021)
Background: The most important prognostic factor in transfusion-dependent beta-thalassemia is cardiac involvement, which is usually evaluated with echocardiography. Methods: In this cross-sectional study (Aprill 2011 to Aprill 2012), conventional echocardiography was used to assess myocardial performance and valvular involvement (by trans-valvular Doppler study) for right and left heart abnormalities in transfusion-dependent beta-thalassemia. Results: Among 60 patients, 43 cases had heart problems, that 26 (43.3%) of them had left myocardial dysfunction and 11 (18.3%) of them had right myocardial dysfunction, 3cases had both RV and LV myocardial dysfunction,(based on LVMPI & RVMPI, respectively). In patients with right myocardial dysfunction, 4 cases had pulmonary hypertension (PH) and 3 had both sided myocardial dysfunction. LVMPI and RVMPI were significantly increased in patients with cardiac involvement (p<0.001). Serum ferritin levels in patients with and without cardiac involvement were 2427±1788 ng/ml and 1573±592 ng/ml, respectively (p=0.008). All 4 patients who had PH, had been splenectomized. In splenectomized and non-splenectomized patients, LVMPI was 0.37 ± 0.11 and 0.38 ±0.1 (p = 0.589), RVMPI was 0.3±0.07 and 0.25±0.39 (p = 0.004), and TR gradient (TRG) was 28±11.8 mmHg and 19.7±5.2 mmHg (p = 0.033), respectively. Mean ferritin level in patients with a history of splenectomy (n=31), was 2525±1968 ng/ml and in patients without the history of splenectomy (n=29), it was 1821±947 ng/ml (p = 0.082). Conclusion: In addition to left-sided heart involvement, conventional echocardiography revealed right-sided heart involvement in transfusion-dependent thalassemia patients that was not correlated with serum ferritin level.in splenectomized patients.